2016
DOI: 10.1177/0146167216647383
|View full text |Cite
|
Sign up to set email alerts
|

Psychologically Adjusted Persons Are Less Aware of How They Are Perceived by Others

Abstract: Focusing on individual differences, we studied three influences on the accuracy of meta-perceptions of personality: (a) projection, that is, relying on one's self-perception; (b) normative meta-insight, that is, relying on the perception of the typical person by others; and (c) distinctive meta-insight, that is, relying on others' perception of one's unique personality attributes. Using a round-robin design, 52 groups of four acquainted students described themselves, three acquaintances, and their meta-percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Thus, rather than being blind to their effect on others, people with distress were acutely aware once they were acquainted. Evidence for the Painfully Aware Hypothesis is in line with a recent finding by Mosch and Borkenau (), who showed that people with higher self‐esteem were less aware of how they were seen by peers. They argued that such a pattern suggests positive affect interferes with analytic processing, a skill that might be necessary for detecting the impressions one makes.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Thus, rather than being blind to their effect on others, people with distress were acutely aware once they were acquainted. Evidence for the Painfully Aware Hypothesis is in line with a recent finding by Mosch and Borkenau (), who showed that people with higher self‐esteem were less aware of how they were seen by peers. They argued that such a pattern suggests positive affect interferes with analytic processing, a skill that might be necessary for detecting the impressions one makes.…”
Section: Discussionsupporting
confidence: 88%
“…Yet, people with more psychopathology symptoms tend to see themselves differently than others see them (Clifton, Turkheimer, & Oltmanns, ; Mosterman & Hendriks, ), suggesting that self‐perceptions probably hinder rather than foster their accuracy. Interestingly, most people are able to make valid distinctions between how they see themselves and how others perceive them, an ability called meta‐insight (Carlson, Vazire, & Furr, ; Gallrein, Carlson, Holstein, & Leising, ; Mosch & Borkenau, ; Oltmanns, Gleason, Klonsky, & Turkheimer, ). Thus, people can effectively use sources of information other than their self‐perceptions to infer the impression they make (e.g., feedback).…”
Section: Interpersonal Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kenny and DePaulo's () more recent review extended this conclusion. Although people are reasonably accurate at discerning how they are viewed in general, they are poor at detecting differences in how they are viewed by specific others (called distinctive meta‐insight by Mosch & Borkenau, ). Thus, the common tendency to perceive that others understand oneself, reflected in convergence between perceivers' self‐views and reflected appraisals, may exaggerate, and perhaps correlate only minimally with, specific others' actual understanding.…”
Section: The Association Between Actual Understanding and Feeling Undmentioning
confidence: 99%